Very low frequency (VLF) phenomena : proceedings of the International Workshop on Coordinated Study of Very Low Frequency (VLF) Phenomena: Global Approach, Barkatullah University, Bhopal, India (November 25-27, 1999) - International Workshop on Coordinated Study of Very Low Frequency (VLF) Phenomena: Global Approach (1999 : Bhopal, India); Hughes, A. R. W.; Ferencz, Csaba, 1941-; Gwal, A. K.; Barkatullah University (New Delhi : Narosa Pub. House, 2003)
Contributed articles presented at the Workshop.
Includes bibliographical references.
Keywords: VLF emissions -- Congresses